Informational and instrumental support related to menstruation: Adolescents’ perspective - Eighty Mardiyan Kurniawati; Nur Anisah Rahmawati; Cahyani Tiara Safitri; Safa Salsabila Hanum (International Journal of Public Health Science (IJPHS), 2022)
Adolescent girls can experience puberty and[a1]  menstruation in their school environment, especially when they decide to study in a boarding school for girls. Schools must provide support for menstrual hygiene therefore adolescent girls can remain productive in their education. The study aims to describe the adolescent perception of informational and instrumental support related to menstruation. The descriptive study was conducted at a single institution-boarding school for girls- in East Java, Indonesia. 236 students in junior high school were asked to fill out a questionnaire. Almost all adolescents had received information about menstruation before they experienced menstruation. Absenteeism due to menstruation was experienced by 35 students with 1-2 days of absence. In terms of informational support, more than 50% of students received information related to menstruation from their teachers. The school did not provide materials on menstrual hygiene on the toilet walls that could be accessed by adolescents. In terms of instrumental support, most adolescents reported that clean water was available but soap for washing hands was not always available. Closed trash cans and access to a sanitary pad are available. According to most of the adolescents, the latrines in their school were easy to clean, but there were still around 10% who stated that the latrines were difficult to clean. Schools need to provide correct information about reproductive health through collaboration with the health office and health education institutions and ensure that facilities for menstrual hygiene are available and can be used by students properly.